Impact Characterization of Safety Helmets Made From Areca Fiber-Reinforced Polyester Composites - Ahmad, Nazli; Arif, Zainal; Arif Adlie, Taufan; Iskandar (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Composite materials are a combination of two or more materials with different properties. Areca fiber, a natural fiber abundant in Indonesia, has the potential to be used as reinforcement in composites with Polyester BTQN 157 resin as the matrix. This study aims to analyze the effect of varying fiber-resin weight fractions (10%, 15%, 20%, 25%, and 30%) on impact strength. Specimens were fabricated using the hand lay-up method and tested using the Charpy impact method according to ASTM standards. The results show that the composite with 20% fiber content achieved the highest impact strength, at 3.193 kJ/m². However, this value remains below the Indonesian National Standard (SNI) requirement for safety helmets, which is 0.00972 J/mm². The produced helmet weighs 470 grams, exceeding the SNI standard (337 ± 5 grams). Although the helmet demonstrated resistance to impact, further research is required to optimize the material composition to fully meet SNI standards.